2019
DOI: 10.1177/1468678319888629
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies of isothermal decomposition of (NH4)4UO2(CO3)3 to uranium oxide

Abstract: The ammonium uranyl carbonate, (NH4)4UO2(CO3)3, is an important material used in UO2 and U3O8 ceramics production for the nuclear fuel fabrication. Thermal study and kinetic analysis of ammonium uranyl carbonate conversion under isothermal conditions has been studied in air atmosphere to obtain the tri-uranium octoxide (U3O8), using muffle furnace equipment, UV–visible spectrophotometer, gas adsorption, Hg porosimetry, laser granulometry, and optic spectroscopy. The textural properties (specific surface area, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 19 publications
5
6
0
Order By: Relevance
“…By analyzing this mass variation, the material balance calculations unequivocally indicated that the AUC compound was (NH 4 ) 4 UO 2 (CO 3 ) 3 . Consequently, our study successfully identified the conditions conducive to the formation of AUC precipitates, which are very similar to the findings reported in the literature [ [37] , [38] , [39] , [40] , [41] , [42] ]. Therefore, to achieve the precipitation of free AUF, a C/U molar ratio greater than six is required.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…By analyzing this mass variation, the material balance calculations unequivocally indicated that the AUC compound was (NH 4 ) 4 UO 2 (CO 3 ) 3 . Consequently, our study successfully identified the conditions conducive to the formation of AUC precipitates, which are very similar to the findings reported in the literature [ [37] , [38] , [39] , [40] , [41] , [42] ]. Therefore, to achieve the precipitation of free AUF, a C/U molar ratio greater than six is required.…”
Section: Resultssupporting
confidence: 86%
“…8 . The typical dTG and TG curves of the AUC decomposition reaction obtained under these conditions are similar to those described in the literature [ [37] , [38] , [39] , [40] , [41] , [42] ]. The dTG and TG curves obtained during AUC decomposition ( Fig.…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations